FAKTOR YANG MEMPENGARUHI HARGA SATUAN BIAYA PEMBANGUNAN INFRASTRUKTUR DI WILAYAH DENGAN AKSESABILITAS TERBATAS - Yamani Yasmin; Dyah Erny Herwindiati; Endah Murtiana Sari (Jurnal Pensil : Pendidikan Teknik Sipil, 2025)
Infrastructure development in Indonesia is a national strategic program that must be achieved because it concerns the people’s livelihoods. The government is currently undertaking various efforts to attain massive-scale infrastructure development throughout the national territory. Central Papua Province is a province in eastern Indonesia that requires infrastructure development to meet the needs and rights of the community to access development and improve community welfare in various fields. The unit price of building materials for infrastructure development that is effective and efficient is crucial in Central Papua, given the limited accessibility, which results in the unit price of infrastructure development being expensive. This study aims to compile factors that influence the high unit price of infrastructure development in Central Papua based on logistics costs. Through quantitative and qualitative methods (mixed methods), this study will produce factors that are considered significant in influencing the high unit cost of infrastructure development. The quantitative method will be carried out through secondary data processing from projects completed from 2020 to 2024 to map the costs considered dominant in influencing the unit price of infrastructure development. Meanwhile, the qualitative method is carried out through in-depth interviews with experts, including government, contractors, and logistics service providers, to confirm factors considered influential in the unit cost of infrastructure development in Central Papua. The results of this study will have a direct impact on the government's efforts to determine the unit cost of infrastructure development based on factors that are considered to have a significant influence.